Sanksi Pidana Adat terhadap Pelaku Tindak Pidana Melarikan Anak Perempuan Dibawah Umur di Desa Selat Kabupaten Batanghari - Islah Islah; Nella Octaviany Siregar; Ade Ardinata (Universitas Batanghari Jambi, 2021)
Special customary law of customary criminal comes from the custom of the community so it is referred to as the law born from below. Customary law as an unwritten law is the basis in determining good and bad behavior in a particular traditional society. Customary law, especially customary criminal law, has certain sanctions if one or more members of the traditional community commit irregularities or actions that are not in accordance with the norms and rules of decency (Adat Law). Article 332 of the Penal Code is understood to be taking away an immature woman with a view to mastering it, by our society is often associated with the term eloping. Eloping itself when it is interpreted simply is between a man and a woman who performs marriage without being approved by his parents or guardians. Taking away an underage woman or child abduction is again widely talked about by the public. Cases of fleeing underage women are spread almost all over Indonesia, our concerns are becoming even greater because the victims of child abduction are the majority of underage girls. To investigate, investigate and dismantle the chain of cases that are quite complicated it takes